Новые патенты центра поддержки технологий и инноваций - Gornostaev V. N. (Relevant lines of scientific research: development prospects, 2017)
it is shown that the patents of specialists of the Center for Support of Technologies and Innovations on the basis of Petrozavodsk University in the first half of 2017 are based on serious scientific research and organization of patent information work.
Keywords: инновации; исследования; университет; патент; research; innovation; patent; university